An Integrated Wearable Sweat Sensing Patch for Passive Continuous Analysis of Stress Biomarkers at Rest. (16th December 2022) - Zhao, Hao; Zhang, Xieli; Qin, Yanxia; Xia, Yong; Xu, Xin; Sun, Xiguang; Yu, Dehai; Mugo, Samuel M.; Wang, Dong; Zhang, Qiang
Abstract: Real‐time monitoring of mental stress biomarkers in sweat provides the possibility to evaluate mental status in a precise manner. In general, wearable sweat sensors suffer from inconvenient sweat collection, low levels of diagnostic biomarkers in sweat, sophisticated signal processing, and challenges with data visualization. To overcome these challenges, herein an integrated wearable sweat‐sensing patch for continuous analysis of stress biomarkers (cortisol, Mg 2+, and pH) at rest is demonstrated. The sweat sensing patch comprised a microfluidic chip, a highly sensitive sensing platform, an on‐site signal processing circuitry (SPCs), and a smartphone installed with a home‐developed display software. The sweat collection at rest is realized using a microfluidic chip without perspiration assistance. A ternary composite electrode is designed to obtain good conductivity, high surface area, and massive reactive sites, thereby yielding excellent electrochemical performances and high sensitivity to trace stress biomarkers. The on‐site SPC has the function of signal transduction, conditioning, processing, and wireless transmission. The detection results can be displayed on a smartphone through the software. This work represents a significant scientific and technological advancement toward indexing mental stress status and can be used as an innovative tool for psychological diagnosis. Abstract : The wearable sweat sensing patch fabricated integrates a microfluidic chip, an electrochemical sensing patch, and an on‐site signal processing circuitry capable of simultaneously detecting cortisol, magnesium ions, and pH in sweat. The detection results can be wirelessly transmitted to smartphones in real time to assess a person's mental health.